Kepuasan Pasien Terhadap Pelayanan Resep Di Apotek KOPKAR Rumah Sakit Budhi Asih Jakarta - Harianto, Harianto; Khasanah, Nana; Supardi, Sudibyo (UI Scholars Hub, 2005)
The pharmaceutical services at a dispensary are prescription dispensing, self-medication and drug information. Patient's satisfaction is an essential factor in improving medicines sale at dispensary. The objective of survey is to know the patient's satisfaction who get the prescription service at Kopkar dispensary. Cross sectional study is conducted by collecting data from 100 adult patients who get the prescription service at Kopkar dispensary on November 2003 by questioner. Respondent are selected by the systematic random sampling. Data were analyzed by comparing between the perception of reality service and the perception of need service using correlation index. The result of this study are: (1) The patients have high satisfaction to the empathy and the cleaning waiting room, (2) The patients have moderate satisfaction to the drug service, the cashier service, the drug information, the drug completed, the drug price, the desk in waiting room, the fan and air conditioning service, and (3) the patients have low satisfaction to the television service.